Management Strategic in Non Profit Organization Pc. PMII Lamongan - M. Furqon Wahyudi (Pascasarjana Manajemen Pendidikan Universitas Gresik, 2023)
The cadreization strategy management of PC PMII Lamongan experienced a major change with the covid 19 outbreak. Calculated by one cadreization period of PMII Lamongan experienced confusion with the cadreization system to be used. This small study provides exposure to the direction of cadreization of PC. PMII Lamongan after the Covid 19 pandemic. Direction of PC cadreization. PMII Lamongan after implementing strategy management experienced a good change, namely by implementing a multi-level cadreization system of strategy. This research uses this type of qualitative research by plunging into the field, data obtained from observations, interviews and documentation. The results of the study found a PC. PMII lamongan has a good cadreization environment, evidenced by the diagram that PMII lamongan cadres increase every year because the environment built by each cadre belongs to a good category, PC. PMII Lamongan in determining the direction of movement for one year has been formed at the beginning, when the branch conference is held. The direction of PMII Lamongan cadreization is neatly wrapped in a cadreization manual that has been endorsed as a guide to local PC cadreization. PMII Lamongan, PC. PMII Lamongan implements a multi-level cadreization system this strategy began when bimtek has been implemented simultaneously rayon cadreization team, commissariat and cabang